Changes of Amide Proton Transfer Imaging in Multiple System Atrophy Parkinsonism Type - Li, Shuhua; Chan, Piu; Li, Chunmei; Chen, Haibo; Chen, Min; Su, Wen; Li, Kai; Lu, Na; Yu, Lu; Chu, Defa; Wu, Pu-Yeh (Frontiers in Aging Neuroscience, 2020)
Multiple system atrophy, an atypical parkinsonism of alpha-synucleinopathies, has no specific biomarker of diagnosis. According to different combinations of symptoms, MSA can be classified as parkinsonism-type MSA (MSA-P) and cerebellar-type MSA (MSA-C)(2), Amide proton transfer (APT) imaging is by far the most studied chemical exchange saturation transfer imaging for its sensitive to mobile protons and peptides in tissue. We hypothesize that APT imaging may be a feasible biomarker of MSA-P. 20 MSA-P patients and 20 age-matched normal controls were enrolled in this study and underwent MR exams on a 3.0T MR scanner. Magnetization transfer spectra at 3.5ppm were acquired at two transverse slices of the head, including the midbrain and the basal ganglia. Mann-Whitney U test was used to compare the asymmetrical magnetization transfer ratio (MTRasym) difference between MSA-P patients and normal controls. The APT MTRasym values of MSA patients in red nucleus (p=0.000), substantia nigra (p=0.000), thalamus (P=0.000) and putamen (p=0.013) were significantly higher than those in normal controls. There was a negative correlation between APT MTRasym and the score of the part III of unified Parkinson disease rating scale (R=-0.338 P=0.044) in putamen, while a positive correlation between the APT MTRasym and the rate of motor symptom progression (R=0.406 p=0.017) in red nucleus. These findings suggest that APT MTRasym changes are found and may be of value in the diagnosis of MSA-P.